Evaluation of dietary quality using Malaysian Healthy Eating Index and its relationships with cardiometabolic risk factors in Malaysian adolescents - Appannah, Geeta; Emi, Nor Aishah; Ahmad Yusin, Nur Athira; Wan, Ying Gan; Mohd Shariff, Zalilah; Shamsuddin, Nurainul Hana; Anuar Zaini, Azriyanti; Appukutty, Mahenderan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: This cross-sectional study aimed to investigate relationships between diet quality assessed by Malaysian Healthy Eating Index (HEI) and cardiometabolic risk factors in adolescents aged 13 years. Methods: 336 adolescents from various public secondary schools provided information on sociodemography and their anthropometric measurements including height (cm), weight (kg) and waist circumference (cm) were measured. Body mass index (BMI) was estimated thereafter. Dietary intakes assessed using a validated adolescent food frequency questionnaire (FFQ) was used to estimate Malaysian HEI. Biomarker parameters including lipid profile, fasting glucose, insulin and insulin resistance were also assessed. Associations of diet quality indicators to cardiometabolic risk factors were examined using regression models. Results: The overall diet quality of the adolescents was rather poor (49%), with a greater percentage of males were found to have low dietary quality score compared to females (56% vs. 39%; p <0.05). While males were more obese, a higher number of females (46.7%) were found to have at least one risk factors for cardiometabolic health compared to males (37.7%). After adjusting for covariates, no significant associations were observed among adolescents in the lowest quartile compared to those in the highest quartile of HEI score for obesity and abdominal obesity, as well as other cardiometabolic risk factors, in both males and females. Conclusion: Despite of poor dietary quality, no significant associations were observed between dietary quality assessed by Malaysia HEI and cardiometabolic risk factors in adolescents. Prospective studies are needed to establish a causal link between dietary patterns and cardiometabolic risk factors during adolescence.